2022
DOI: 10.1108/ijse-11-2021-0674
|View full text |Cite
|
Sign up to set email alerts
|

Early human capital: the driving force to economic growth in island economies

Abstract: PurposeThe paper investigates into the human capital–economic growth nexus by arguing that investment in early education and health helps in achieving higher economic growth. Early investment in human capital matters most for economic growth than the increase in human capital over the years.Design/methodology/approachA dynamic vector error correction model (VECM) together with the impulse response function and variance decomposition are used on data for Mauritius from 1983 to 2019. The paper distinguishes betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
(80 reference statements)
1
1
0
2
Order By: Relevance
“…This may be due to the increase in government spending on secondary education and the increasing interest in it because it qualifies for university admission, and then its impact appears in the labor market. These results are consistent with eco-nomic theory and consistent with empirical studies by [1,13,15,[52][53][54] on Africa.…”
Section: Cointegration Testsupporting
confidence: 91%
See 1 more Smart Citation
“…This may be due to the increase in government spending on secondary education and the increasing interest in it because it qualifies for university admission, and then its impact appears in the labor market. These results are consistent with eco-nomic theory and consistent with empirical studies by [1,13,15,[52][53][54] on Africa.…”
Section: Cointegration Testsupporting
confidence: 91%
“…The study utilized GDP per capita, labor factor (unemployment as a percentage of total labor force), physical capital (GFCF), the pupil-teacher ratio in pre-primary education, and life expectancy at birth as variables to measure this effect. The study demonstrated that public investment in early childhood education and health improves educational and health outcomes and promotes economic growth [31].…”
Section: Time Series Literature Reviewmentioning
confidence: 95%
“…A historical https://doi.org/10.56294/sctconf2023515 alignment with the political interests of the public sector was identified as a necessary and sufficient condition for growth through diversification. Furthermore, Ben Jabeur et al, (2021) (53) delved into the impact of institutional and macroeconomic conditions on aggregate corporate failure in a sample of European countries from 2004 to 2017. Their comparative analysis involving fuzzy sets and partial least squares regression revealed that countries with low corruption indices and high levels of government effectiveness could mitigate insolvency.…”
Section: Methodsmentioning
confidence: 99%
“…Ketika negaranegara beralih menuju ekonomi yang berbasis pengetahuan, maka keberadaan sumber daya manusia yang sangat terampil menjadi semakin penting (Rosendo Silva et al, 2018). Sudah banyak penelitian yang menyoroti Human Capital sebagai penentu utama pertumbuhan ekonomi (Ali et al, 2021;Anetor, 2020;Apergis et al, 2022;Duan et al, 2022;Ibrahim, 2018;Neeliah & Seetanah, 2016;Sehrawat & Giri, 2017;Tahir et al, 2020;Tandrayen Ragoobur & Narsoo, 2022). Namun pada kondisi saat ini peran dari health capital secara intens menjadi fokus penelitian dari akademisi (Isreal Akingba et al, 2018).…”
Section: Pendahuluanunclassified
“…yang berasumsi bahwa akumulasi modal akan selalu memicu pertumbuhan ekonomi, yang akan memicu peningkatan produksi barang dan jasa. Hasil penelitian ini memperkuat penelitian sebelumnya(Addi & Abubakar, 2022;Amidu et al, 2016;Sarwar et al, 2021;Tandrayen Ragoobur & Narsoo, 2022;Thaddeus et al, 2021) yang menyatakan bahwa investasi dalam bentuk gross fixed capital formation berpengaruh positif dan signifikan terhadap pertumbuhan ekonomi. model FMOLS, DOLS dan CCR menunjukkan hasil variabel health expenditure per capita mempunyai pengaruh yang positif dan signifikan terhadap GDP per capita hasil ini konsisten dengan perhitungan menggunakan model ARDL.…”
unclassified